2017
DOI: 10.1038/s41598-017-05810-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload exacerbates age-associated cardiac hypertrophy in a mouse model of hemochromatosis

Abstract: Cardiac damage associated with iron overload is the most common cause of morbidity and mortality in patients with hereditary hemochromatosis, but the precise mechanisms leading to disease progression are largely unexplored. Here we investigated the effects of iron overload and age on cardiac hypertrophy using 1-, 5- and 12-month old Hfe-deficient mice, an animal model of hemochromatosis in humans. Cardiac iron levels increased progressively with age, which was exacerbated in Hfe-deficient mice. The heart/body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…By reducing intracellular iron levels, cardiomyocytes protect from iron overload-induced oxidative stress. In patients with hereditary hemochromatosis and patients with β-thalassemia, iron overload exacerbated cardiac hypertrophy 8,39 . Intracellular ferrous iron-also called labile iron-is readily oxidized by the Haber-Weiss reaction, resulting in cellular ROS formation 40 ; in the hearts of older rats, ferritin levels are increased, possibly as a protective response to oxidative stress from ROS accumulation 36,41 .…”
Section: Discussionmentioning
confidence: 99%
“…By reducing intracellular iron levels, cardiomyocytes protect from iron overload-induced oxidative stress. In patients with hereditary hemochromatosis and patients with β-thalassemia, iron overload exacerbated cardiac hypertrophy 8,39 . Intracellular ferrous iron-also called labile iron-is readily oxidized by the Haber-Weiss reaction, resulting in cellular ROS formation 40 ; in the hearts of older rats, ferritin levels are increased, possibly as a protective response to oxidative stress from ROS accumulation 36,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The attenuated Y. pestis Pgm − strain was lethal to an individual with hereditary hemochromatosis manifesting iron overload in tissues [11]. The Hfe −/− mice display the iron overload phenotype that was similarly observed in humans with hereditary hemochromatosis [36,39]. Therefore, we used Hfe −/− mice to further evaluate safety profiles of KIM10(pCD1Ap) and YPS19(pCD1Ap) strains by i.m.…”
Section: Safety Assessment Of Y Pestis Mutant Strainsmentioning
confidence: 99%
“…2), which may partially explain the paradoxical outcomes of HRT in postmenopausal women. Iron overload in postmenopausal women has been shown to increase the risk of hot flashes [51], osteoporosis [52], metabolic syndrome [53], cardiac hypertrophy and cardiovascular complications [54,55] and brain aging and neurodegenerative disorders [56] among others. Both iron and E2 have been separately implicated in diseases, but whether an E2-iron axis is at play has never been considered.…”
Section: E2-iron Axis In Diseasementioning
confidence: 99%
“…The progressive decline of endogenous E2 levels during menopause is a risk factor for heart disease [54,55], hence the use of HRT to lower the risk of heart disease in postmenopausal women [74][75][76]. However, well-designed studies have indicated that HRT does not lower the risk of heart disease in postmenopausal women [55,77,78].…”
Section: E2-iron Axis and Cardiovascular Complicationsmentioning
confidence: 99%